2009
DOI: 10.1007/s11738-009-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses of Hyacinth bean (Lablab purpureus) to salinity stress

Abstract: Effect of salinity on Hyacinth bean, Lablab purpureus (HA-4 cultivar) was evaluated in 10-day old seedlings with 100-500 mM NaCl over 72 h of exposure. The stress reduced dry and fresh weight, leaf surface area, root and shoot length, total chlorophyll, and RWC. Oxidative stress markers, H 2 O 2 , glutathione, TBARS, proline, ascorbic acid, total phenols, and total soluble sugar contents were significantly elevated. Salinity enhanced antioxidant enzymes, POX, and GR activities and reduced that of CAT in concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 55 publications
2
36
0
1
Order By: Relevance
“…Ksouri et al (2007) reported that salt-challenged halophyte Cakile maritima produced significanlty higher amount of polyphenol in its leaves. Souza and Devaraj (2010) reported that the total phenol content of the salt-stressed leaves exhibited a concentration-dependent increase from 100-400 μM NaCl during the first 24 h of exposure in hyacinth bean. In the medicinal herb Echinacea angustifolia, the salinity of the nutrient solution significantly enhanced the root contents of chlorogenic acid, cynarin and cichoric acid in hydroponically grown planlets (Montanari et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ksouri et al (2007) reported that salt-challenged halophyte Cakile maritima produced significanlty higher amount of polyphenol in its leaves. Souza and Devaraj (2010) reported that the total phenol content of the salt-stressed leaves exhibited a concentration-dependent increase from 100-400 μM NaCl during the first 24 h of exposure in hyacinth bean. In the medicinal herb Echinacea angustifolia, the salinity of the nutrient solution significantly enhanced the root contents of chlorogenic acid, cynarin and cichoric acid in hydroponically grown planlets (Montanari et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The proven antioxidant activity of phenolics allows them to act as ROS scavenging agents. As a result, their synthesis is generally triggered in response to biotic/abiotic stresses and especially under salt stress conditions (Souza and Devaraj, 2010). Except for their role in reducing the detrimental effects of salinity and drought, phenolic compounds exhibit wide range of physiological properties such as antiallergic, antiatherogenic, anti-inflammatory, antimicrobial, antithrombotic ones (Balasundram et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Under saline conditions plant accumulates osmoprotector solutes such as soluble amino acids, soluble sugars, proline and glycinebetaine (D'Souza and Devaraj 2010;Bayuelo-Jimenez et al 2012;Shawky 2013a, 2014a). These organic solutes can accumulate to high levels without disturbing intracellular biochemistry, protecting sub-cellular structures, mitigating oxidative damage caused by free radicals, and maintaining the enzyme activities (Yokoi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Soil salinization also induces the synthesis of osmoprotectants such as glycinebetaine and proline Shawky 2013, 2014a), which contribute to osmotic adjustment, to stabilize the active conformation of cytoplasmic enzymes, and to scavenge hydroxyl radicals, thereby mitigating oxidative damage caused by salinity stress (Ashraf and Foolad 2007). The relationship between salt tolerance and an efficient antioxidant system has been assessed in many plant species (D'Souza and Devaraj 2010;Mallik and others 2011;Shawky 2013, 2014b); whereas the behavior of the antioxidant system in salt-stressed plants treated with effective microorganisms (EM) has received no attention. The present study on the antioxidative response of saltaffected plants treated by EM will be a new and first report.…”
Section: Introductionmentioning
confidence: 99%